L’improvisation dans le travail enseignant, entre défiance et ressource - Françoise Lantheaume (Recherches en Éducation)
This article deals with the place and meaning of improvisation in the work teachers in France by exploring a corpus of interviews from the perspective of pragmatic sociology and activity analysis. The confrontation between the different discourses of the teachers and their practices shows that far from the generally expressed defiance, improvisation takes several forms and can represent a resource for the development of the grammar of the activity, the genre and the professional style of the teachers.